1988
DOI: 10.1002/cber.19881211127
|View full text |Cite
|
Sign up to set email alerts
|

Polar effects in radical addition reactions: Borderline cases

Abstract: Methyl radicals substituted by one ester or nitrile group are on the borderline between nucleophilic and electrophilic behavior. In addition reactions of these borderline radicals to styrenes, polar effects of both, electron-withdrawing and electron-donating substituents at the alkeae, increase the rates. But these polar effects are smaller compared to those of nucleophilic or electrophilic radicals. In consequence, the stability of the radicals formed during the addition of the borderline radicals to styrenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
28
1
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 17 publications
6
28
1
1
Order By: Relevance
“…The philicities of the radicals generated in these reactions significantly influence the scope of the transformations, wherein favorable matching of the alkene and alkyl radical polarities is essential. 7 Efficient reactivity is accomplished by employing electronically activated alkenes and further enhanced with superstoichiometric loadings of the other coupling partners and of strong oxidants. An alternative approach to the three-component carboamination of alkenes via Pd-catalysis was also reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The philicities of the radicals generated in these reactions significantly influence the scope of the transformations, wherein favorable matching of the alkene and alkyl radical polarities is essential. 7 Efficient reactivity is accomplished by employing electronically activated alkenes and further enhanced with superstoichiometric loadings of the other coupling partners and of strong oxidants. An alternative approach to the three-component carboamination of alkenes via Pd-catalysis was also reported.…”
mentioning
confidence: 99%
“…These represent challenging substrate classes, as the radical additions are significantly slower compared to terminal vinylarenes. 7 Aliphatic alkenes are challenging, as subsequent oxidation is less favorable. However, we hypothesized the oxocarbenium intermediate could promote this key step.…”
mentioning
confidence: 99%
“…[9] While facing the difficulties of developing cascade photoredox imino functionalizations of electron-poor O-aryl oximes, [6] we realized that an inherent chemical reactivity issue was associated with the envisaged catalytic cycle.T he nitrogen radicals A are electrophilic species and undergo facile exo-trig cyclizations (Scheme 1C). [10] However,u pon ring closure,they generate the nucleophilic carbon radical B, which benefits from polar effects [11] in the reaction with SOMOphiles X À Y. This process leads to the formation of the imino-functionalized product C and the radical YC.T his radical, even though it is not involved in any bond-forming event, controls the fate of our photoredox manifold.…”
mentioning
confidence: 99%
“…Ryu and Alper pioneered this area and showed that SET from an acyl radical to Mn III proceeded at a significantly faster rate than the same process involving alkyl radicals. [50] This specificity enabled them to describe an original 4-CR that judiciously exploits the multiple characteristics of Mn III salts (Scheme 24): 1) MnA C H T U N G T R E N N U N G (OAc) 3 first generates an electrophilic malonyl radical [51] that adds onto olefin 80; 2) the ensuing nucleophilic radical 80 i readily adds onto CO, and 3) MnA C H T U N G T R E N N U N G (OAc) 3 oxidizes the resulting acyl radical 80 ii into an acylium cation 80 iii that is immediately trapped by the nucleophilic fourth component H 2 O.…”
Section: Multicomponent Radical-ionic Reactionsmentioning
confidence: 99%